ANALISIS DETERMINAN RASIO PAJAK DI INDONESIA TAHUN 1992– 2023 : Studi Pada Tahun 1992-2023 - Khotimah, Siti Husnul; Tsani, Luthfi Ibnu (Jurnal Riset Ilmu Ekonomi, 2025)
The tax ratio is an important indicator in measuring the performance of a country's taxation sector against Gross Domestic Product (GDP). In Indonesia, the tax ratio is still relatively low and has not reached the minimum standard recommended by the World Bank. This study aims to examine the factors that can affect the tax ratio in Indonesia in the short and long-term using the Error Correction Model (ECM) method. The variables used in the analysis of this study consist of per capita income, economic growth, inflation, unemployment, and the Corruption Perception Index (CPI). The estimation results show that in the long run, per capita income and unemployment have a negative and significant effect on the tax ratio, while economic growth and inflation have a positive and significant effect. CPI shows a negative but insignificant effect. In the short term, only economic growth and inflation have a positive and significant effect on the tax ratio, while other variables are not significant. The ECT coefficient is negative and significant, indicating the existence of an adjustment mechanism towards long-term equilibrium.